2019
DOI: 10.18800/economia.201902.0003
|View full text |Cite
|
Sign up to set email alerts
|

Productivity Growth: Patterns and Determinants “Across” the World

Abstract: This is the background paper for the productivity extension of the World Bank's Long-Term Growth Model (LTGM). Based on an extensive literature review, the paper identifies the main determinants of economic productivity as innovation, education, market efficiency, infrastructure, and institutions. Based on underlying proxies, the paper constructs indexes representing each of the main categories of productivity determinants and, combining them through principal component analysis, obtains an overall determinant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 97 publications
(122 reference statements)
3
3
0
Order By: Relevance
“…In our steady-state analysis we have found that the steady state value of capital positively depends on the TFP level. Therefore, in agreement with relevant studies showing a positive relationship between the development stage of the economy and the associated TFP (see, Kim and Loayza, 2019), it is logical to expect that developing economies will be facing a lower steady state value of capital than the developed economies. According to Proposition 1, in such economies pollution will monotonically increase with income.…”
Section: Transitional Dynamicssupporting
confidence: 85%
“…In our steady-state analysis we have found that the steady state value of capital positively depends on the TFP level. Therefore, in agreement with relevant studies showing a positive relationship between the development stage of the economy and the associated TFP (see, Kim and Loayza, 2019), it is logical to expect that developing economies will be facing a lower steady state value of capital than the developed economies. According to Proposition 1, in such economies pollution will monotonically increase with income.…”
Section: Transitional Dynamicssupporting
confidence: 85%
“…(The World These results also confirm the conclusions of other empirical studies that the physical capital is considered the main source of growth for developing countries, with a minimal contribution of the TFP, and that the poor economic performance of these countries could be attributed to the low and insufficient productivity growth. Examples of these studies include Pipitone 2009, and Abu-Qarn, A., and S. Abu-Bader 2007 This result is consistent with the results of Kim and Loayza (2019) in which education had the highest contribution to the variance of TFP growth estimated at 49% followed by institutions and market efficiency for the case of developing countries during the period (2004-2014) ▪ The weak contribution of both the infrastructure and innovation in explaining the variance of the TFP in developing countries. In the case of infrastructure, this can be explained partly by the variation between the developing countries in the level of development of their infrastructure, but it is also highly related to what Hulten (1996) referred to as efficiency of infrastructure, that is the adequacy of managing and maintaining the existing infrastructure.…”
Section: Results: A) Total Factor Productivity Growthsupporting
confidence: 70%
“…The estimates of TFP derived from Table 2 are almost consistent with the growth rate of TFP of Sub-Saharan African countries estimated by Kim and Loayza (2019) for the period 2004-2014. The estimates of TFP derived show the same pattern of TFP growth.…”
Section: Derivation Of Tfpsupporting
confidence: 73%